Democratizing the economics debate : pluralism and research evaluation - D'Ippoliti, Carlo (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"More than a decade since the global financial crisis, economics does not exhibit signs of significant change. Mainstream economists act on an idealized image of science, which includes the convergence of all perspectives into a single supposed scientific truth. Democratizing the Economics Debate shows that this idealized image both provides an inadequate description of what science should be and misrepresents the recent past and current state of economics. Economics has always been characterized by a plurality of competing perspectives and research paradigms, however there is evidence of a worrying global involution in the last forty years. Even as the production of economics publications has exploded, the economics debate is becoming less plural and increasingly more hierarchical. Among several causes, the tendency to conformism has been exacerbated in recent years with the use of formal schemes of research quality evaluation. This book documents how such schemes now cover more than half of all economists worldwide, and reviews the impact of biased methods of research evaluation on the stunting of levels of pluralism in economics. The book will be of interest to anyone who worries for the state of the democratic debate. As experts who intervene in the public debate, economists must assure society that they are working in the best possible way, which includes fostering a wide and fair scientific debate. It is this test of social legitimacy that economics currently fails"--
OCLC-licensed vendor bibliographic record.
Keywords: Economics -- Research; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Economics / Theory